Pengaruh Profesi Tukang Cukur dalam Transformasi Kampung Peundeuy, Banyuresmi, Garut - Nishlah, Hilyatun; Hapsarani, Dhita (Paradigma: Jurnal Kajian Budaya, 2021)
Being professional barbers from Garut—known as ASGAR, short for Asli Garut, which means ‘of Garut origin’—has been the main source of income for most men residing in Kampung Peundeuy, Banyuresmi Village, Garut Regency, West Java. The profession is considered so successful in providing financial welfare for the villagers and improving their social status that many of the residents decide to leave the village to expand their business elsewhere, especially in Jakarta and other big cities in West Java. This phenomenon has intensified since the 2000s until the residents finally dub Kampung Peundeuy as a “barber village” in West Java. In order to preserve their hometown’s reputation as a “barber village”, the residents feel the need to preserve and pass on their shaving and hairdressing skills to their relatives and children. As a result, what was once only a common profession now has been considered as part of the village’s tradition. Furthermore, the barber profession has spurred various changes in Kampung Peundeuy, including their livelihood, cultural identity, and social life. Therefore, in order to examine the relationship between barber as a profession dan village transformation, the research attempted to answer these two questions: (1) How did the profession became a tradition among Kampung Peundeuy’s residents? and (2) How has the barber profession stimulated the transformation of the village? This research incorporated thoughts proposed by Koentjaraningrat (1981) who studied community problems, by Luji (2020) who examined profession as a form of culture, and McGee (2001 & 2008) who proposed the theory of semi-urbanization. This study applied the qualitative method, which included the ethnographic method, non-participatory observation, and interviews to collect data. This study is in line with Luji’s (2020) finding that the tradition of becoming barbers was produced and consumed by the residents of Kampung Peundeuy for years by means of power relation among family members. Families encouraged their male members (parents, husbands, sons, or sons-in-law) to become barbers because the job is considered profitable. Moreover, further changes do not occur naturally but are spurred by semi-urbanization when residents carry their profession to big cities. Semiurbanization (McGee 2008) encourages the phenomenon of desakota (literally “urbanvillage”) which describes the influence of urban lifestyle on Kampung Peundeuy. Thus, it can be concluded that the barber profession influences the transformation of Kampung Peundeuy, and this can occur due to the strong encouragement among its residents to both pass down the hairdressing skills to the next generation and to enter the profession.